PEMBERIAN PUPUK ORGANIK CAIR (POC) DENGAN DOSIS BERBEDA TERHADAP KELIMPAHAN Chlorella sp. - Muhammad Nur; Rosyadi; Fakhrunnas MA Jabbar; Khairul Hadi (DINAMIKA PERTANIAN, 2023)
Liquid Organic Fertilizer (POC) has a high amount of nutrients that can be used as a nutrient source for the growth of Chlorella sp. This research aimed to determine the effect of Liquid Organic Fertilizer on the growth and abundance of Chlorella sp. cells and to obtain the optimal dosage of Liquid Organic Fertilizer for the growth of Chlorella sp. This research was conducted at the Laboratory of Microalgae and Fish Nutrition, Faculty of Agriculture, Islamic University of Riau. The research used a Completely Randomized Design (CRD) with four treatments, specifically giving POC doses of 2.5cc, 5cc, 7.5cc, and 10cc/l of water with three repetitions. The measured changer is growth and abundance, biomass, and parameters of the culture media such as temperature, pH, nitrate, and phosphate. The research results obtained the highest abundance of Chlorella sp. cells. amounted to 7,966,667 cells/ml at the POC dose of 5 cc/l of water, and the peak was on the 16th day, the lowest dose of 2.5 cc/l was 6,483,333 cells/ml, cell-specific growth rate Chlorella sp. during the study ranged from 0.074-0.087/hr. The highest amount of biomass was 0.3629 gr/l, parameters of the culture media such as temperature ranged from 26-30oC, pH of 6-8, nitrate 1.976-4.802 mg/l and phosphate 0.360-2.680 mg/l.